Fremdes in Anatolien : Importgüter aus dem Ostmittelmeerraum und Mesopotamien als Indikator für spätbronzezeitliche Handels- und Kulturkontakte. (Schriften zur vorderasiatischen Archäologie., 2017)
During the Late Bronze Age (approx. 1500–1200 BC), an intensive exchange of goods developed in the Near East and the eastern Mediterranean region, which was of a diverse nature and led to the first "globalization". It was largely supported by the palaces of the various great empires of Babylonia via Egypt to Mycenaean Greece and their vassals in the Levant and on Cyprus. The largest part of Anatolia was ruled by the Hittite Empire at this time.In the present study, all known from the eastern Mediterranean region (Aegean, Cyprus, Egypt, Levant) and foreign objects from Mesopotamia that were found in Late Bronze Age contexts in Anatolia. These are objects made of different materials that can be assigned to different groups of objects, including vessels, figurines, reliefs, jewellery, weights, parts of furniture, seals, game boards. All objects are typologized and with regard to their chronological position development and their origin. Furthermore, the find contexts are evaluated in order to be able to determine their functional significance. On the basis of these foreign goods, it can be shown what type and intensity Anatolia's relations with the various neighboring regions were, whereby a precise distinction must be made between the different areas within Anatolia. In this way, Anatolia is fundamentally included in the discussion about the exchange network of the Late Bronze Age world for the first time.